Hematological, biochemical, and histopathological evaluation of the Morus alba L. leaf extract from Brunei Darussalam: acute toxicity study in ICR mice - Fauzi, Ahmad; Kifli, Nurolaini; Noor, Mohd; Hamzah, Hazilawati; Azlan, Azrina (ScopeMed, 2024)
Background: Studies have reported that the phytochemical content of Mulberry (Morus alba Linn.) is influenced by the area where it grows. On the other hand, the study of the bioactivity and toxicity of mulberry leaves from Brunei Darussalam still needs to be completed. In particular, the investigation regarding the safe dose for Mulberry’s application from Brunei Darussalam has yet to be studied. Hence, toxicity information must be considered even though the community has used it for generations. Aim: This study investigated Morus alba ethanolic leaf extract (MAE) to observe the acute toxicity in mice. Methods: In particular, this study utilized 12 female Institute of Cancer Research mice, 8 weeks old, divided into 2 groups: the control group and the MAE group (2,000 mg/kg single dose). Physiology, hematology, biochemistry, and histology were analyzed during the study. Results: The examination result indicated no mortality and behavioral changes throughout the testing period. However, the mice developed mild anemia and leukopenia, followed by decreased numbers of neutrophils, lymphocytes, and monocytes. In addition, the mice developed a mild hepatocellular injury, indicated by significant (p < 0.05) elevations of both alanine aminotransferase (ALT) and aspartate transaminase (AST). The histopathological findings of the liver were also consistent with the increment of ALT and AST, indicating mild hepatocellular necrosis through the eosinophilic cytoplasm and pyknosis (p > 0.05). Conclusion: It was evident that a single oral administration of MAE was not lethal for mice (LD50, which was higher than 2,000 mg/kg). However, the administration of high doses of MAE must be carefully considered.